Examination of Students' Perceptions of the Selection of Science Subjects in High School Credit System and Their Reasons for Selection - 신동선; 박종근 (International Journal of Advanced Culture Technology(IJACT), 2023)
We investigated and analyzed students' perceptions of their choice of science subjects in the high school credit system and the reasons for their choice. To achieve this, the selection of science subjects was investigated for the second year of S high school over the past three years. Students selected an average of 1.54 science subjects, and it was found that the rate of selection of science subjects was gradually increasing by year. Students chose high in the order of life science I, earth science I, chemistry I, physics I, etc. in the science subject group. Students who wish to enter the natural and engineering fields chose life science I, chemistry I, physics I, etc., while, students who wish to enter the humanities society chose society and culture, life science I, ethics and thought, etc. On the other hand, the reason for choosing science subjects was 'related to college admission', followed by 'aptitude and interest', 'career and real life help', etc. physics I, chemistry I, etc., were high in the subjects selected according to the 'related to college admission'. The subjects selected according to 'aptitude and interest' were high in life science I, earth science I, etc. Physics I, chemistry I, etc. are recognized as subjects necessary for college entrance, and life science I, earth science I, etc., are found to be related to their interests and aptitudes.